Meeting report: 32nd International Conference on Antiviral Research - Tramontano, Enzo; Tarbet, Bart; Spengler, Jessica R; Seley-Radtke, Katherine; Meier, Chris; Jordan, Robert; Janeba, Zlatko; Gowen, Brian; Gentry, Brian; Esté, José A; Bray, Mike; Andrei, Graciela; et al. (Antiviral research, 2019)
The 32nd International Conference on Antiviral Research (ICAR), sponsored by the International Society for Antiviral Research (ISAR), was held in Baltimore, Maryland, USA, on May 12-15, 2019. This report gives an overview of the conference on behalf of the Society. It provides a general review of the meeting and awardees, summarizing the presentations, and their main conclusions from the perspective of researchers active in many different areas of antiviral research and development. As in past years, ICAR promoted and showcased the most recent progress in antiviral research, and continued to foster collaborations and interactions in drug discovery and development. The 33rd ICAR will be held in Seattle, Washington, USA, March 30th-April 3rd, 2020.
Keywords: farmaceutická chemie; internacionalita; výzkum; Drug Discovery; antivirové látky; Humans; virové nemoci; objevování léků; Antiviral Agents; Technology, Pharmaceutical; Virus Diseases; farmaceutická technologie; Research; Chemistry, Pharmaceutical; lidé; Internationality